Strategi Keberhasilan Mediator Dalam Menangani Kasus Perceraian Di Pengadilan Agama Kota Malang - Muhammad Iqbal Ismaili Asya; Muhammad Fajrul Huda; Irwan Wahyudi (Muhammadiyah University of Surabaya, 2025)
The strategy of mediators in handling divorce cases at the Religious Court of Malang City is crucial due to the increasing number of divorce cases in the region. This research is an empirical legal study conducted at the Religious Court of Malang City, using a socio-legal approach. Data were collected through interviews with several judge-mediators and non-judge mediators. The findings show that the success rate of mediation in divorce cases at the Religious Court remains relatively low. However, there are still some cases where mediation has been successful—either fully resolved, partially resolved based on mutual agreements, or unsuccessful altogether. The results also reveal that the strategies employed by mediators include providing religious guidance and moral education to the disputing parties. In addition, mediators encourage self-reflection by helping the parties recognize the value of family harmony and consider the long-term consequences of divorce, particularly its impact on family members. These strategies aim to raise awareness among divorcing couples so that they can make more thoughtful decisions regarding their marital disputes. Overall, the role of the mediator is not only to facilitate agreement but also to foster reconciliation and prevent further family breakdown whenever possible.